Integrated bioinformatics approaches to investigate alterations in transcriptomic profiles of monkeypox infected human cell line model - Gangga Anuraga; Jilu Lang; Do Thi Minh Xuan; Hoang Dang Khoa Ta; Jia-Zhen Jiang; Zhengda Sun; Sanskriti Dey; Sachin Kumar; Ayushi Singh; Gagan Kajla; Wei-Jan Wang; Chih-Yang Wang (Elsevier, 2024)
Background: The recent re-emergence of the monkeypox (mpox) epidemic in nonendemic regions has raised concerns regarding a potential global outbreak. The mpox virus (MPV) is a smallpox-like virus belonging to the genus Orthopoxvirus (family: Poxviridae). Although studies suggest that MPV infection suppresses the Toll-like receptor-3- and tumor necrosis factor-α-related signaling pathways, whether MPV regulates other immune-related pathways remains unclear. Methods: In this study, two distinct temporal patterns were used for establishing an MPV-infected human immortal epithelial cancer cell line (HeLa). These two durations 2 and 12 h of incubation were selected to identify the coregulated genes and pathways affected by MPV infection. Results: The use of the Gene Ontology framework, Kyoto Encyclopedia of Genes and Genome database, and MetaCore software yielded valuable insights. Specifically, various pathways were found to be enriched in HeLa cells infected with MPV for 2 and 12 h. These pathways included Notch, CD40, CD95, hypoxia-inducible factor-1-α, interleukin (IL)− 1, IL-6, phosphoinositide 3-kinase, nuclear factor-κB, mitogen-activated protein kinase, and oxidative stress-induced signalling pathways. Clusters and pathways of metabolism and viral replication cycles were significantly associated with the 2-hour infection group. This association was identified based on the regulation of genes such as HSPG2, RHPN2, MYL1, ASPHD2, CA9, VIPR1, SNX12, MGC2752, SLC25A1, PEX19, and AREG. Furthermore, clusters and pathways related to immunity and cell movement were found to be associated with the 12-hour infection group. This association was identified based on the regulation of genes such as C1orf21, C19orf48, HRK, IL8, GULP1, SCAND2, ATP5C1, FEZ1, SGSH, TACC2, CYP4X1, MMP1, CPB1, P2RY13, WDR27, PRPF4, and ENDOD1. Conclusions: This study can improve our understanding of the mechanisms underlying the pathophysiology and post-infection sequelae of mpox. Our findings provide valuable insights into the various modes of MPV infection.